1997
DOI: 10.1007/s002530051095
|View full text |Cite
|
Sign up to set email alerts
|

The ability of soil-borne fungi to degrade organophosphonate carbon-to-phosphorus bonds

Abstract: The ability of a wide variety of soil-borne fungal strains to degrade four structurally different compounds containing P-C bonds, namely the naturally occurring amino acid ciliatine, the popular herbicide glyphosate, phosphonoacetic acid and 2-amino-3-phosphonopropionic acid, was studied in order to show that soil fungi may play an important role in the biodegradation of organophosphonates. Most of the strains appeared to utilize ciliatine as the sole source of phosphorus for growth. Only a limited number of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…the same medium was used but without K 2 hPo 4 to serve as the control (medium in the absence of phosphate). thus, when glyphosate was used as the sole source of phosphorus, K 2 hPo 4 was replaced by glyphosate at a final concentration of 10 mmol/L (14). All glassware was washed with 1 mol/l hcl and rinsed with deionized water to remove contaminating phosphate before use and then glyphosate was added after medium sterilization.…”
Section: Growth Profilesmentioning
confidence: 99%
“…the same medium was used but without K 2 hPo 4 to serve as the control (medium in the absence of phosphate). thus, when glyphosate was used as the sole source of phosphorus, K 2 hPo 4 was replaced by glyphosate at a final concentration of 10 mmol/L (14). All glassware was washed with 1 mol/l hcl and rinsed with deionized water to remove contaminating phosphate before use and then glyphosate was added after medium sterilization.…”
Section: Growth Profilesmentioning
confidence: 99%
“…Few attempts have been made to investigate the biodiversity of microorganisms capable of degrading organophosphonates (26), and studies have concentrated mainly on gram-negative, mesophilic bacteria, although recent work has attempted to redress this imbalance (9,14,19). While the isolation, biochemical characterization, and taxonomic description of thermophilic microbial strains have proceeded apace in recent years (18), biodegradation studies with such microorganisms are relatively scarce, and studies with organophosphonates are nonexistent.…”
mentioning
confidence: 99%
“…The germination count, mean height of the maize 4WAP, number and weight of cobs harvested from the treated plots were 35, 288.8 plants/hectare, 75.19cm, 26, 666.8 cobs /hectare and 3, 682.8g respectively in the first phase of the study, which are higher than the 28,600.4 plants/hectare, 59.5cm, 15, 916.8 cobs/hectare and 1, 985.2g recorded in the second phase. This can be attributed to the lingering effects of the herbicides in the experimental plots (Myers et al, 2016), and the physiochemical changes caused to the soil by the use of the herbicides (Ayansina and Oso, 2006;Liu et al, 1991;Sprankle, et al 1975;Krzysko-Lupicka et al, 1997). Studies conducted by Myers et al (2016) showed that herbicides persist in the soil longer than previously reported, and so the effects of the herbicides applied during the first phase of the study can easily extend to the second phase of the study.…”
Section: Discussionmentioning
confidence: 97%